RELIGIOUS AND CULTURAL CONSTRUCTS OF THE SASAK COMMUNITY AGAINST CHILD MARRIAGE PRACTICES: Case Study in Sengkerang Village, Central Lombok - Siti Aminah (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2023)
In the context of understanding the religion and culture of the Sasak community, there are no provisions that clearly regulate the age of marriage. So cases of child marriage become difficult to stop. Despite the presence of the Child Marriage Law as a very important legal instrument in protecting children's rights and preventing child marriage. This research is field research using qualitative methods through a phenomenological approach. This approach is used in an effort to describe field facts based on the phenomenologist's experience without intervention from the researcher. So this method does not focus on statistical measurements or calculations, but rather emphasizes a deep understanding of the characteristics and context of the phenomena studied using qualitative data. The results of the research show that: In the view of religious communities there are no clear provisions regarding the age requirements for marriage. However, the measurements used to determine whether it is permissible or not still give rise to various interpretations. Meanwhile, in the cultural context of the Sasak community, the existence of Merariq culture is the main support that there are also no provisions regarding the age that is considered valid for carrying out this tradition. It only refers to the readiness and agreement of both parties, even in some cases Merariq is also carried out even without the woman's consent. So laws regarding marriage age are often violated because society is still guided by religious understanding and cultural practices.